A non-linear complex diffusion-based edge and structure preserving zooming technique for MRI and ultrasound images. (11th July 2011) - Srivastava, Rajeev; Gupta, J.R.P.; Parthasarthy, Harish
In this paper, a non-linear complex diffusion-based edge and structure preserving image zooming technique for Magnetic Resonance Imaging (MRI) and ultrasound images is proposed. The proposed method performs regularisation, edge and structure preservation of digital medical MRI and ultrasound images, which were initially zoomed using one of the linear interpolation methods such as nearest-neighbour, bilinear and bi-cubic. For digital implementations, the proposed model is discretised using finite differences schemes. The scheme is implemented in MATLAB 7.0 and tested for various MRI and ultrasound images. A comparative analysis of the proposed scheme with the standard existing schemes have been performed in terms of Mean Square Error (MSE), Peak Signal-to-Noise Ratio (PSNR), Correlation Parameter (CP), Mean Structure Similarity Index Map (MSSIM) and histogram analysis. The obtained results justify the applicability of the proposed scheme.